SOCIAL AND CULTURAL DYNAMICS IN THE AGE OF GLOBALIZATION: UNIFICATION OR HETEROGENEITY - E. Avdeev (Гуманитарные и юридические исследования)
The article deals with the processes of interaction and transformation of national cultures in modern globalizing world. The dynamics of social and cultural changes is characterized by a number multidirectional processes. These are: the formation of global mass culture, trends towards isolationism and hybridization of cultures. The author analyzes the changing nature of interaction between local cultures under the conditions of the global media space and amplification of heterogeneity of national cultures.